HUBUNGAN USIA IBU DAN LAMA PEMAKAIAN DENGAN PENINGKATAN BERAT BADAN PADA AKSEPTOR KB SUNTIK 3 BULAN DI BPM RUSMIATI OKTA PALEMBANG - Rezah Andriani; Heny Oktarina (Jurnal Kesehatan Abdurrahman, 2015)
One of the side effects of injectable KB is weight gain, weight gain is influenced by the duration of use and the mother’s age.Formulation of the problem in this research was "was there a relationship between maternal age and the duration of use with increasing weight at 3-month injectable acceptors".The study aimed to determine the duration of use and the mother’s age who had been using contraception injections 3 months and determined the relationship between maternal age and the duration of use with weight gain. The study used survey analytic with cross sectional approach, sampling would be carried out by non-random sampling method with the technique of "Accidental sampling" where the sampling would be conducted using cases or respondents who happened to be available. Study used a questionnaire instrument.These results indicate that respondents who experienced an increase in body weight by 22 respondents (66.6%), younger respondents who experienced an increase in body weight were 17 respondents (51.5%), respondents who had been using injectable acceptors 3 months who experienced an increase in body weight by 19 respondents (57.6%). Chi-square test results showed no significant association between maternal age with increased body weight obtained p value of 0.010 <α (0.05), and no significant association between the duration of use with weight gain obtained p value of 0.002 <α (0,05). It’s suggested to the health workers in order to give health information by counseling mothers about family planning in particular Injectable Contraceptives, and can improve the quality and service. Salah satu efek samping dari KB suntik adalah peningkatan berat badan. Peningkatan berat badan dipengaruhi oleh lama pemakaian dan usia ibu. Rumusan masalah dalam penelitian ini adalah “Apakah ada hubungan usia ibu dan lama pemakaian dengan peningkatan berat badan pada akseptor KB suntik 3 bulan?” Penelitian ini bertujuan untuk mengetahui lama pemakaian dan usia ibu yang telah memakai KB suntik 3 bulan serta mengetahui hubungan usia ibu dan lama pemakaian dengan peningkatan berat badan. Penelitian ini menggunakan metode Survey analtik dengan pendekatan cross sectional, Pengambilan sampel akan dilakukan dengan metode non-random sampling dengan teknik “Accidental sampling” dimana pengambilan sampel akan dilakukan dengan menggunakan kasus atau responden yang kebetulan tersedia. Instrumen penelitian menggunakan kuesioner. Hasil penelitian ini menunjukan bahwa responden yang mengalami peningkatan berat badan sebanyak 22 responden (66,6%), responden yang berusia muda dan mengalami peningkatan berat badan sebanyak 17 responden (51,5%), responden yang telah lama menjadi akseptor KB suntik 3 bulan dan mengalami peningkatan berat badan sebanyak 19 responden (57,6%). Hasil uji Chi-square menunjukan ada hubungan yang bermakna antara usia ibu dengan peningkatan berat badan diperoleh p value sebesar 0,010 < (0,05), dan ada hubungan yang bermakna antara lama pemakaian dengan peningkatan berat badan diperoleh p value sebesar 0,002 < (0,05).